Abuso Sexual Contra Crianças e Adolescentes no Contexto Intrafamiliar no Amazonas - Figueredo, Ana Caroline Lopes (Brasil, 2022)
This is a research with the objective of analyzing the reported cases of sexual abuse against children and adolescents in the state of Amazonas, understanding the context in which these crimes occur. As for the methodology, the research assumes the contribution of qualitative approaches, without excluding quantitative aspects, under the inspiration of the historical-critical method. It was found that the social construction of childhood is a recent issue and, for a long time, children were considered a miniature of adults, however, without the same rights. With the Federal Constitution of 1988 and the Statute of Children and Adolescents, children and adolescents became subjects of law, despite this, it is noted that, even today, legal precepts lack effectiveness. Rights are violated, demanding political responses that enable the social protection of children and adolescents. It was also identified that the data reveal that sexual violence, specifically rape, is the crime with the highest incidence among children and adolescents, with girls under the age of 14 being the main victims. From the data obtained, it was observed that the social worker, as a result of his training in the constant struggle for social rights, by integrating a multidisciplinary team and working with issues in which social vulnerability and violation of rights predominate, becomes a professional of great relevance to ensure comprehensive, humanized and dignified care for victims of sexual violence.